The Penetration of Human Rights into the Agenda of the European Union - Hubert Smekal (Czech Journal of International Relations, 2014)
The article documents the process of the increase in the relevance of fundamental rights in the European Union and calls attention to the fact that it is gradually approaching an important point whose attainment would have a considerable impact on the nature of the EU. The text traces the development of the EU’s powers and activities in setting the norms related to fundamental rights, and deciding about their application, control and enforcement. The states have been reluctant to permit the Union to intervene into their domestic human rights affairs which are not connected to the EU’s competences. Nevertheless, its recent activities indicate that the EU is starting to get more say even in this cautiously guarded domain of domestic competence.